CBSE
X
Y - X
Y
N
(-∞, 1)
[1, ∞]
R
(1, ∞)
a = b = c = 1
B.
Tips: -
અહીં f(x) = g(x) આપેલ છે
∴ f(1) = g(1)
∴ a + b + c = 3 ... (1)
વળી, f(2) = g(2) = 3(2) + 1 = 7 થાય.
∴ a(2)2 + b(2) + c = 7
∴ 4a + 2b + c = 7 ... (2)
તેમજ f(3) = g(3) = 3(3) + 1 = 10 પરથી,
a(3)2 + b(3) + c = 10
∴ 9a + 3b + c = 10 ... (3)
સમીકરણ (2) તથા (3) પરથી, 5a + b = 3 મળે.
∴ b = 3 - 5a સમીકરણ (2) માં મૂકતાં c = 1 + 6a મળે.
∴ (1) પરથી, a + 3 - 5a + 1 + 6a = 3
∴ a = -
તથા c = 1 + 6 મળે.
3x2 + x +24
x2 + x + 24
2017
2014
2016
2015
f(x) + f(y)
f(x)•f(y)
(f(x))2
f(x)/(f(y)
x
x2
0
1
i - c, ii - a, iii - b
i - b, ii - c, ii - a
i - a, ii - b, iii - c
i - a, ii - c, iii - b
110
116
106
96